INTEGRATION OF INTELLECTUAL INTELLIGENCE, MORALS, AND LEARNING ACHIEVEMENT: A MODERN ISLAMIC EDUCATION PERSPECTIVE - Ariesi Apriyanti; M. Sirozi (SOSIOEDUKASI, 2025)
This article discusses the integration of intellectual intelligence (IQ), morals, and learning achievement from the perspective of modern Islamic education. In the context of contemporary education, students’ academic success is generally measured based solely on cognitive ability, while spiritual and moral dimensions receive less attention. As a result, education tends to produce individuals who are intellectually competent but lacking in values and ethics. This study aims to examine the concept of holistic education based on Islamic values that balances cognitive and spiritual aspects in shaping students’ character and academic achievement. This research uses a literature review method by analyzing relevant scholarly sources, including modern psychological theories on IQ as well as Islamic educational thought from Syed Muhammad Naquib al-Attas and Imam al-Ghazali. The findings show that IQ plays an important role in academic performance, but it is not the only factor determining learning success. From an Islamic perspective, true success is achieved when intellectual intelligence (‘aql) is accompanied by moral maturity (khuluq), as emphasized in QS. Al-Mujadilah verse 11 and the hadith on the importance of knowledge with proper adab. Al-Attas’s concept of adab and Al-Ghazali’s process of tazkiyatun nafs affirm that true education aims to form individuals who are both intellectually capable and morally virtuous. Therefore, the paradigm of modern Islamic education needs to be directed toward an integrative-holistic learning model that combines cognitive, spiritual, and ethical dimensions to develop a generation that is high-achieving, well-mannered, and refined in character.